THE EFFECT OF SMALL GROUP WORK STRATEGY ON STUDENTS’S ACHIEVEMENT IN WRITING PROCEDURE TEXT - Asrina Sari Siregar and Masitowarni Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study attempts to discover the effect of applying Small Group Work Strategy on students’ achievement in writing procedure text. It was conducted by using experimental research design. The population of this research was the nineth (IX) grade students of SMP N 1 Padang Bolak Julu which consists of 3 parallel classes with the total number of students is 90. The samples of this research were taken by random sampling through lottery technique. The result was class IX1 consisted of 30 students became the experimental group and class IX3 consisted of 30 students became the control group. The experimental group was taught by Small Group Work Strategy while the control group was taught by using individual work strategy. The instrument was used to collect the data was writing procedure text. After the data were analyzed, it was found that the value of t-observed was 3.37 with the degree of freedom (df) = 58 at the level significance 0.05. it means that t-observed was higher than t-table (3.37 > 2.00. Therefore, the null hypothesis (Ho) is reected and the hypothesis alternative (Ha) is accepted.